2000
DOI: 10.1093/emboj/19.4.642
|View full text |Cite
|
Sign up to set email alerts
|

The Sos1 and Sos2 Ras-specific exchange factors: differences in placental expression and signaling properties

Abstract: Targeted disruption of both alleles of mouse sos1, which encodes a Ras-specific exchange factor, conferred mid-gestational embryonic lethality that was secondary to impaired placental development and was associated with very low placental ERK activity. The trophoblastic layers of sos1 -/-embryos were poorly developed, correlating with high sos1 expression in wild-type trophoblasts. A sos1 -/-cell line, which expressed readily detectable levels of the closely related Sos2 protein, formed complexes between Sos2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1
26

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 50 publications
5
94
1
26
Order By: Relevance
“…Grb2 is constitutively associated with Sos1, and the phenotype of Grb2 and Sos1 knockout mice was similar (16,17,46). However, though Grb2 expression is required in several classical models of negative selection (HY + male mice, SEB injection, and anti-CD3ε injection) (47,48), as discussed previously, Sos1 was dispensable for these same processes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Grb2 is constitutively associated with Sos1, and the phenotype of Grb2 and Sos1 knockout mice was similar (16,17,46). However, though Grb2 expression is required in several classical models of negative selection (HY + male mice, SEB injection, and anti-CD3ε injection) (47,48), as discussed previously, Sos1 was dispensable for these same processes.…”
Section: Discussionmentioning
confidence: 59%
“…The precise role of the two Sos isoforms in T-cell development, however, has not been established. Sos2 −/− mice are phenotypically normal, but their thymocyte development has not been assessed (15), whereas Sos1 −/− mice die in utero of a placental defect (16,17).…”
mentioning
confidence: 99%
“…Because Gasp could compete with Sos for binding to Grb2, existence of Gasp would likely inhibit negative selection, which does not explain the current phenotype well. However, there is no direct evidence that Sos is required for thymic selection, because Sos1 deletion is embryonic lethal (31), and Sos2-deficient mice showed no phenotype (32). Although an earlier study using Grb2 ϩ/Ϫ mice suggested Grb2 is involved in negative selection but not in positive selection (8), recent results from lck-Cre driven Grb2 conditional deficient mice suggests that Grb2 is required for positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in fibroblasts, it does not appear that this pathway is dominant, because Gab1-deficient fibroblasts display stark defects in Erk signaling (45), whereas Erk signaling defects in Sos1-deficient fibroblasts are less striking (46) and Sos2-deficient fibroblasts do not have Erk signaling defects (47). This may in part be explained by functional redundancy between the two mammalian Sos members, although this redundancy does not exist in all tissues (46). It seems likely that fibroblasts predominantly use the Gab1 pathway for Ras activation, whereas other systems activate Ras primarily through Sos (43).…”
Section: Figmentioning
confidence: 99%